1989
DOI: 10.1111/j.1939-0025.1989.tb01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and individuality: A study of Malay children.

Abstract: Malay parents of 40 infants and preschool children were interviewed using translations of temperament questionnaires by Thomas and Chess, and by Carey. Similarities and differences between Malay children and previously studied American children are discussed, and relationships suggested among temperament ratings and Malay child‐rearing practices and values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Similar to cross-cultural studies that treat culture as a contextual variable, ours shows that variations in temperament are related to parental ethnotheories (Banks, 1989;deVries, 1984;deVries & Sameroff, 1984;Harkness & Super, 1992;Shwalb et al, 1994;Super & Harkness, 1982, 1986b. We found that parental ethnotheories were related to core concepts of world view and that even within a cultural community, such as the Yucatec Maya, differences in ecological context may result in variations of ethnotheories which, in turn, may be reflected in temperament characteristics.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar to cross-cultural studies that treat culture as a contextual variable, ours shows that variations in temperament are related to parental ethnotheories (Banks, 1989;deVries, 1984;deVries & Sameroff, 1984;Harkness & Super, 1992;Shwalb et al, 1994;Super & Harkness, 1982, 1986b. We found that parental ethnotheories were related to core concepts of world view and that even within a cultural community, such as the Yucatec Maya, differences in ecological context may result in variations of ethnotheories which, in turn, may be reflected in temperament characteristics.…”
Section: Discussionsupporting
confidence: 69%
“…However, in this setting the population was not exposed to extreme environmental conditions. Banks (1989) related significant differences between Malay and US and Chinese infants to cultural child-rearing practices and values and rejected the notion of Pan Asian temperamental tendencies (e.g., Weissbluth, 1982). Shwalb and colleagues (Shwalb, Shwalb, & Shoji, 1994 develop their own scale based on lists of behaviours generated by middle-class mothers.…”
Section: Infant and Child Temperament Across Cultural Communitiesmentioning
confidence: 99%
“…Among Indians, one large‐scale, longitudinal study in Australia has found that Indian immigrants were similar to Western European infants, and were less likely to have a “difficult” temperament as compared to infants of parents born in Greece, Middle Eastern countries, and East Asian countries (Prior et al., ). On the other hand, Malay babies were found to be less regular, less adaptable, less approachable, and lower in threshold when compared to American babies in another small‐scale study (Banks, ). Cultural differences also have been acknowledged in the temperament of young infants (Nugent, Lester, & Brazelton, ).…”
mentioning
confidence: 86%
“…A few studies on temperament involving Asian infants and children, native as well as immigrant, have produced differing conclusions (Ahadi, Rothbart, & Ye, ; Banks, ; Bhat et al., ; DiPietro, Novak, Costigan, Atella, & Reusing, ; Hsu, Soong, Stigler, Hong, & Liang, ; Prior, Garino, Sanson, & Oberklaid, ). This is not surprising because of the prevailing differences in the temperament traits in various populations.…”
mentioning
confidence: 99%
“…Such studies, conducted mainly by means of psychometric tests on children and adolescents at different ages, refer mostly to Thomas and Chess' theory of temperament (see, e.g. Banks, 1989;Hsu, Soong, Stigler, Hong & Liang, 1981;Kohnstamm, 1989;Kyrios, Prior, Oberklaid & Demetriou, 1989;Prior, Kyrios & Oberklaid, 1987;Skuy, Westaway & Snell, 1986;see, also, Iwawaki, Hertzog, Hooker & Lerner, 1985;Windle, Iwawaki & Lerner, 1988). In these studies, the assumption of equivalent diagnostic measures is adopted, however, often without sufficient data supporting this supposition.…”
Section: Introductionmentioning
confidence: 99%